1998
DOI: 10.1111/j.1749-7345.1998.tb00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Propagation of Mutton Snapper Lutjanus analis, A New Candidate Marine Fish Species for Aquaculture

Abstract: Wild‐caught mutton snapper Lutjanus analis, a high‐value marine food fish species, matured in flow‐through seawater (36 g/L) tanks after 3 yr in captivity. On 31 May 1995, a female with a mean oocyte diameter of 382 μm was injected with human chorionic gonadotropin (HCG) (500 IU/kg body wt.) followed 24 h later by a second injection (1,000 IU/kg body wt.). At the time of the second injection, three males were injected with HCG (500 IU/ kg body wt.). Voluntary spawning occurred 33 h after the first injection, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
0
31

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 21 publications
4
35
0
31
Order By: Relevance
“…Reef-associated fish represent almost half of the total catch by weight, and the mutton snapper is one of the main targets of this fishery (FRÉDOU;FERREIRA, 2005). Because of its high commercial value and the current overexploitation of its natural stocks, L. analis has been identified as one of the best prospects for aquaculture (WATANABE et al, 1998), and preliminary studies in floating net cages have suggested that production of this fish is viable (BENETTI et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Reef-associated fish represent almost half of the total catch by weight, and the mutton snapper is one of the main targets of this fishery (FRÉDOU;FERREIRA, 2005). Because of its high commercial value and the current overexploitation of its natural stocks, L. analis has been identified as one of the best prospects for aquaculture (WATANABE et al, 1998), and preliminary studies in floating net cages have suggested that production of this fish is viable (BENETTI et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the culture of snappers (Lutjanidae family) has been developed throughout the world because of declines in wild stocks combined with a consistent high demand and market value (Watanabe et al 1998, Benetti et al 2002, Garcia-Ortega 2009. Some lutjanid species, such as Lutjanus argentimaculatus, Lutjanus johnii, Lutjanus russelli and Lutjanus sebae, are currently farmed in Pakistan, China, Singapore, Malaysia, Thailand and Philippines (Hong and zhang 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some studies have reported effects of hCG on breeding behaviour. In male mutton snapper (Lutjanus analis) a single hCG injection stimulated spermiation and induced high fertilization rates (Watanabe et al, 1998a). In Japanese eel (Anguilla japonica) weekly hCG injections stimulated active courtship behaviour before spermiation (Dou et al, 2007).…”
Section: Introductionmentioning
confidence: 99%